2013
DOI: 10.11113/jt.v65.2198
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mechanical Properties of High Performance Concrete with Alum Sludge as Partial Cement Replacement

Abstract: Alum sludge (AS) is a by-product of water treatment plants that use aluminum salts as a primary coagulant, and is the most widely generated water treatment residual/sludge worldwide. It usually contains colloidal alum hydroxides that are often amorphous species. The present paper examines the influence of AS powder as partial Portland cement type I replacement on the mechanical properties of high-performance concrete (HPC). AS with 90% fineness was passed through a 45 µm sieve (No. 325).The present study used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…It was shown that slump value increased with an increasing percentage of AS added in concrete mixes. Addition of 15% AS produced the highest value of slump, 80 mm, compared to the control concrete mixture, with 60 mm [4]. A similar test was done later to analyse the influence of TAASA on the properties of multi-blended binders of cement with samples having TAASA content varies from 0% up to 25% [5].…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…It was shown that slump value increased with an increasing percentage of AS added in concrete mixes. Addition of 15% AS produced the highest value of slump, 80 mm, compared to the control concrete mixture, with 60 mm [4]. A similar test was done later to analyse the influence of TAASA on the properties of multi-blended binders of cement with samples having TAASA content varies from 0% up to 25% [5].…”
Section: Introductionmentioning
confidence: 95%
“…al. [4], analysed the high-performance concrete with raw alum sludge addition on the effect of its physical and mechanical properties. Results show that the drinking water sludge is best to be used at 6% replacement of cement across all ages of the curing period.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Goncalves et al, 2004) (Tantawy, 2015) determined the calcination temperature of alum sludge at 800 0 C and stated that it is adequate to enhance its pozzolanic properties. Also investigations were conducted and reported on reusing of AS by other researchers (Alqam et al, 2011;Zamora et al, 2008;Owaid et al, 2014;Sales et al, 2011) (Mohammed et al, 2013) (Awab et al, 2012;Miroslav, 2008).…”
Section: Introductionmentioning
confidence: 99%